EFEKTIVITAS METODE LEARNING COMMUNITY DALAM PEMBELAJARAN BERBICARA MAHASISWA PENDIDIKAN BAHASA DAN SASTRA INDONESIA STKIP PUANGRIMAGGALATUNG SENGKANG - Nur Rahmi; Yetti Anita (Jurnal Akrab Juara, 2018)
This study aims to describe the learning outcomes of speech through the method of Learning Community and the effectiveness of Learning Community method of Indonesian Language and Literature Education at High School of Teacher Training and Education Puangrimaggalatung Sengkang. The location of this research is located at the campus of Teachers Training and Education College Puangrimaggalatung Sengkang. The results showed that effective learning community was used in improving the speaking skill of STKIP Puangrimaggalatung Sengkang students. This is based on the results of data analysis showing that the average test results of students speaking skills that follow the learning in the class that apply learning community is higher than the results of students' speaking skills tests that follow the learning in the class that does not apply learning community. Keywords: Learning community, learning to speak.